A case of a superficial circumflex iliac perforator‐intercostal artery perforator (SCIP‐ICAP) compound flap for necrotizing soft tissue infection. Issue 12 (10th September 2020) - Furuse, Kiichi; Kato, Motoi; Morishita, Yuya; Kumagai, Tomoyo; Nakatsukasa, Shuichi; Kuwata, Tomoyuki
Abstract: Even in NSTI patients with many comorbidities, it is possible to save both the life and the limb by thorough debridement and suitable reconstruction. SCIP‐ICAP compound flap can be versatile for a massive defect of an upper extremity. A Case of a Supercharged Compound Flap for Necrotizing Soft Tissue Infection Abstract : Even in NSTI patients with many comorbidities, it is possible to save both the life and the limb by thorough debridement and suitable reconstruction. SCIP‐ICAP compound flap can be versatile for a massive defect of an upper extremity. A Case of a Supercharged Compound Flap for Necrotizing Soft Tissue Infection.